An Analysis of the Effects of Capital, Labor, and Information Technology on the Revenues of Milkfish-Product MSME in Gresik Regency - Rahmawati, Lili; Sri Muljaningsih (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to examine (1) the effect of business capital on the income of milkfish processed MSMEs in Gresik District; (2) the effect of labor on the income of milkfish processed MSMEs in Gresik Regency; (3) the effect of information technology on the income of milkfish processed MSMEs in Gresik Regency. The research employe a descriptive quantitative method on multiple variables. Data collection was conducted through questionnaires distributed to 40 milkfish processed MSMEs in Gresik Regency. Cross-sectional multiple regression analysis, including regression analysis tests, classical assumption tests, and hypothesis tests, was utilized. The findings indicate that (1) capital has a positive and significant impact on the income of milkfish-processed MSMEs in Gresik Regency; (2) labor has a positive but insignificant impact on the income of milkfish-processed MSMEs in Gresik Regency; (3) information technology has a negative and insignificant impact on the income of milkfish-processed MSMEs in Gresik Regency.